Child emergency assistance training for health cadres in Rowocacing Village, Kedungwuni, Pekalongan - Siti Rofiqoh; Windha Widyastuti; Tri Sakti Wirotomo; Yuni Sandra Pratiwi; Dwi Fijianto; Isyti'aroh Isyti'aroh (Universitas Muhammadiyah Magelang, 2023)
Health cadres are the driving forces of posyandu. One of the roles of health cadres is to provide health education. Various factors cause this role to be less than optimal, including the factor of lack of knowledge. The purpose of this activity is to increase the knowledge of health cadres about first aid at home for children with health problems so that cadres are able to disseminate knowledge of mothers to the community, especially groups, and children. Activities in the form of training for cadres on the first aid at home for children with health problems in Rowocacing Village, Kedungwuni District, Pekalongan. Participants in the activity were 19 cadres. The method of activity carried out by providing cadre training for 2 days on emergency material in children includes choking, diarrhea, sprains, and injuries. Training activities are carried out using the learning lecture method, question and answer, discussion, demonstration, and re-demonstration by the participants. Evaluation is done in writing and demonstration. The average initial knowledge score was 48.3 and the final average score was 80.1, so it can be concluded that there is an increase in cadres' knowledge about first aid at home for children with health problems.